2006
DOI: 10.1007/s10995-006-0168-x
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptomatology and Mental Health Help-Seeking Patterns of U.S.- and Foreign-Born Mothers

Abstract: Our research suggests that previous "global estimates" on Asian American mental health underestimated sub-ethnic group differences. More efforts are needed to overcome the barriers in mental health services access and utilizations, especially in minority and foreign-born populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
7
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 40 publications
5
107
7
2
Order By: Relevance
“…In the US, Weir et al showed that rates of timely and adequate perinatal care were nonoptimal in a Medicaid managed care population [46]. Huang et al showed that racial minorities and foreign-born mothers were less likely to consult doctors for their emotional problems compare to non-Hispanic white mothers [47]. Our study found that poor SRMH was associated with later registration of pregnancy and greater tobacco use.…”
Section: Discussionmentioning
confidence: 44%
“…In the US, Weir et al showed that rates of timely and adequate perinatal care were nonoptimal in a Medicaid managed care population [46]. Huang et al showed that racial minorities and foreign-born mothers were less likely to consult doctors for their emotional problems compare to non-Hispanic white mothers [47]. Our study found that poor SRMH was associated with later registration of pregnancy and greater tobacco use.…”
Section: Discussionmentioning
confidence: 44%
“…23 Racial/ ethnic minorities and foreign-born mothers may also be less likely than non-Hispanic white mothers to seek medical care for their emotional problems. 33 Regardless of the mechanism, this finding suggests that partner support may have salience with regard to racial/ethnic disparities in pregnancy outcomes. Targeting fathers has been proposed as a key strategy to mitigate racial and ethnic disparities in birth outcomes, 34,35 and further inquiry into the role of the partner and fathers during pregnancy on such disparities is needed.…”
Section: Discussionmentioning
confidence: 88%
“…Kim, 2009) are higher than those found in studies of Americans overall (Radloff, 1977) and European Americans (Henderson et al, 2005). In a national study of mothers of young children (from six to 22 months old), more Korean American mothers (44.4%) reported depressive symptoms than non-Hispanic white American mothers (38.5%) (Huang, Wong, Ronzio, & Yu, 2007).…”
Section: Korean American Depressive Symptomsmentioning
confidence: 80%